2019
DOI: 10.18203/issn.2455-4529.intjresdermatol20193238
|View full text |Cite
|
Sign up to set email alerts
|

Over the counter medication: a study among dermatology outpatients

Abstract: <p class="abstract"><strong>Background:</strong> Over-the-counter (OTC) medicine or non-prescription medicine refer to medicine that you can buy without a prescription from a health care professional. The prevalence, clinical patterns and causative agents of cutaneous drug reactions vary among different populations. The most widely used over the counter medication in dermatological practice are topical steroids. The main objective is to know awareness among the people about over the counter m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…This finding was similar to the study conducted by Varshney et al [9], which showed fungal infection (59.5%) as the most common indication. The study by Birudala et al showed that most patients used topical medications for acne (39.7%), which was different from our research [3].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding was similar to the study conducted by Varshney et al [9], which showed fungal infection (59.5%) as the most common indication. The study by Birudala et al showed that most patients used topical medications for acne (39.7%), which was different from our research [3].…”
Section: Discussioncontrasting
confidence: 99%
“…The male to female ratio (M: F) was 0.9:1. Our finding was similar to that of the study conducted by Birudala et al (M: F = 0.6:1) [3]. Over-the-counter, freely available fairness creams are responsible for the raised numbers of female patients in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations